Beyond fossil calibrations: realities of molecular clock practices in evolutionary biology - Hipsley, Christy A.; Müller, Johannes (Frontiers in Genetics, 2014)
Molecular-based divergence dating methods, or molecular clocks, are the primary neontological tool for estimating the temporal origins of clades. While the appropriate use of vertebrate fossils as external clock calibrations has stimulated heated discussions in the paleontological community, less attention has been given to the quality and implementation of other calibration types. In lieu of appropriate fossils, many studies rely on alternative sources of age constraints based on geological events, substitution rates and heterochronous sampling, as well as dates secondarily derived from previous analyses. To illustrate the breadth and frequency of calibration types currently employed, we conducted a literature survey of over 600 articles published from 2007 to 2013. Over half of all analyses implemented one or more fossil dates as constraints, followed by geological events and secondary calibrations (15% each). Vertebrate taxa were subjects of nearly half of all studies, while invertebrates and plants together accounted for 43%, followed by viruses, protists and fungi (3% each). Current patterns in calibration practices were disproportionate to the number of discussions on their proper use, particularly regarding plants and secondarily derived dates, which are both relatively neglected. Based on our survey, we provide a comprehensive overview of the latest approaches in clock calibration, and outline strengths and weaknesses associated with each. This critique should serve as a call to action for researchers across multiple communities, particularly those working on clades for which fossil records are poor, to develop their own guidelines regarding selection and implementation of alternative calibration types. This issue is particularly relevant now, as time-calibrated phylogenies are used for more than dating evolutionary origins, but often serve as the backbone of investigations into biogeography, diversity dynamics and rates of phenotypic evolution.